THE IMPACT OF CREDIT RESTRUCTURING ON BANK HEALTH LEVELS IN MALUKU (CASE STUDY AT PT. BANK MALUKU MALUT) - Purimahua, Sarlotha Y.; Leunupun, Pieter; Tomasila, Mozes; Manufury, Bartha A.; Kesamay, Charolina (Ridwan Institute, 2024)
Bank Maluku Malut (Malut) is a bank operating in the Malukuku region which also experiences